Robotic control of a photometric telescope - Van Heerden, Hendrik Petrus (Department of Astronomy, 2015)
The objective of this project was to design and implement the telescope control software for the Alan Cousins Telescope (ACT), a robotic telescope at the Sutherland, South Africa, site of the South African Astronomical Observatory (SAAO). The approach adopted involved a high level of modularisation of the software and the use of software simulators in an effort to foster rapid software development and enable more rigorous software testing. Significant attention was also paid to new and emerging technologies and how these may be used within the specific context of robotic telescope control software. The software now acts as a demonstration platform for those technologies that were implemented.